Dosimetric comparison of distal esophageal carcinoma plans for patients treated with small‐spot intensity‐modulated proton versus volumetric‐modulated arc therapies. Issue 7 (21st May 2019) - Liu, Chenbin; Bhangoo, Ronik S.; Sio, Terence T.; Yu, Nathan Y.; Shan, Jie; Chiang, Jennifer S.; Ding, Julia X.; Rule, William G.; Korte, Shawn; Lara, Pedro; Ding, Xiaoning; Bues, Martin; et al.
Abstract : Background: Esophageal carcinoma is the eighth most common cancer in the world. Volumetric‐modulated arc therapy (VMAT) is widely used to treat distal esophageal carcinoma due to high conformality to the target and good sparing of organs at risk (OAR). It is not clear if small‐spot intensity‐modulated proton therapy (IMPT) demonstrates a dosimetric advantage over VMAT. In this study, we compared dosimetric performance of VMAT and small‐spot IMPT for distal esophageal carcinoma in terms of plan quality, plan robustness, and interplay effects. Methods: 35 distal esophageal carcinoma patients were retrospectively reviewed; 19 patients received small‐spot IMPT and the remaining 16 of them received VMAT. Both plans were generated by delivering prescription doses to clinical target volumes (CTVs) on phase‐averaged 4D‐CT's. The dose‐volume‐histogram (DVH) band method was used to quantify plan robustness. Software was developed to evaluate interplay effects with randomized starting phases for each field per fraction. DVH indices were compared using Wilcoxon rank‐sum test. For fair comparison, all the treatment plans were normalized to have the same CTVhigh D95% in the nominal scenario relative to the prescription dose. Results: In the nominal scenario, small‐spot IMPT delivered statistically significantly lower liver Dmean and V30Gy[RBE], lung Dmean, heart Dmean compared with VMAT. CTVhigh dose homogeneity and protection of other OARs were comparable between the two treatments. In terms of plan robustness, the IMPT and VMAT plans were comparable for kidney V18Gy[RBE], liver V30Gy[RBE], stomach V45Gy[RBE], lung Dmean, V5Gy[RBE], and V20Gy[RBE], cord Dmax and D 0.03 c m 3, liver Dmean, heart V20Gy[RBE], and V30Gy[RBE], but IMPT was significantly worse for CTVhigh D95%, D 2 c m 3, and D5% ‐D95%, CTVlow D95%, heart Dmean, and V40Gy[RBE], requiring careful and experienced adjustments during the planning process and robustness considerations. The small‐spot IMPT plans still met the standard clinical requirements after interplay effects were considered. Conclusions: Small‐spot IMPT decreases doses to heart, liver, and total lung compared to VMAT as well as achieves clinically acceptable plan robustness. Our study supports the use of small‐spot IMPT for the treatment of distal esophageal carcinoma.